(untitled) (World Science, 2024)
The article presents the requirements for polymer mixtures made on the basis of methyl methacrylate for the arrangement of thin-layer pavements of the bridge deck. The pavement on bridges is an important structural element of the structure, the condition of which affects the overall safety of the entire structure. Given the constant increase in traffic volume and the load on the street network, materials that guarantee reliable operation of the roadway of bridge structures should be used to increase the durability of road surfaces. Road pavement is a key structural element for ensuring the safety and comfort of vehicular traffic, in particular due to its flatness, low noise level and roughness, which guarantees the proper coefficient of adhesion to the tires of vehicles while driving. However, it should be noted that during operation, such a coating is easily exposed to negative factors that lead to its premature deformation.